ITGA5 is associated with prognosis marker and immunosuppression in head and neck squamous cell carcinoma - Jianmin Liu; Yongkuan Wang; Xi Chen; Xiaofang Chen; Meng Zhang (BMC, 2024)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is a major tumor that seriously threatens the health of the head and neck or mucosal system. It is manifested as a malignant phenotype of high metastasis and invasion caused by squamous cell transformation in the tissue area. Therefore, it is necessary to search for a biomarker that can systematically correlate and reflect the prognosis of HNSCC based on the characteristics of head and neck tumors. Methods Based on TCGA-HNSCC data, R software was used to analyze gene expression, correlation, Venn diagram, immune invasive and immunosuppressive phenotypes respectively. The intrinsic effect of ITGA5 on the malignant phenotype of HNSCC cells was verified by cell experiments. Immunohistochemical images from The Human Protein Atlas (THPA) database display the differences in the expression of related proteins in HNSCC tissues. Based on functional enrichment and correlation analysis, the prognostic value of ITGA5 for HNSCC was explored, and the expression level of ITGA5 may affect the chemotherapy of targeting the PI3K-AKT. Results In this study, the target gene ITGA5 may be identified as a valuable prognostic marker for HNSCC. The results of enrichment analysis showed that ITGA5 was mainly involved in the dynamic process of extracellular matrix, which may affect the migration or metastasis of tumor cells. Meanwhile, ITGA5 may be closely related to the infiltration of M2 macrophages, and its secretory phenotypes TGFB1, PDGFA and PDGFB may affect the immunosuppressive phenotypes of tumor cells, which reflects the systemic influence of ITGA5 in HNSCC. In addition, the expression levels of ITGA5 were negatively correlated with the efficacy of targeting PI3K-AKT chemotherapy. Conclusion ITGA5 can be used as a potential marker to systematically associate with prognosis of HNSCC, which may be associated with HNSCC malignant phenotype, immunosuppression and chemotherapy resistance.